Inverse problem for porosity estimation during solidification of TNT - Caldeira, Aldélio Bueno; Jaccoud, Bruno dos Reis; Guedes, Rodrigo Otávio de Castro (Acta Scientiarum. Technology, 2016)
Â In the present study, the porosity formed during the solidification process is estimated by an inverse problem technique based on particle swarm optimization. The effective heat capacity method is adopted to model the heat transfer problem. The transient-diffusive heat transfer equation is solved numerically by the finite volume method with an explicit scheme, employing the central difference interpolation function. The solution of the direct problem is compared to reference solutions. The model is applied to trinitrotoluene (TNT) solidification process. The results show that the proposed procedure was able to estimate the porosity for different Stefan numbers. The analysis of the heat flux in the mold is indicated to predict the porosity formation during the casting process.